Socio-environmental characterization of the environmental protection area of Itapiracó, São Luís - MA - Cristine Costa Carvalho , Jéssica; Erick Brito de Sousa , Carlos (Seven Editora, 2023)
The present study seeks to characterize the Environmental Protection Area (APA) of Itapiracó, from the theoretical survey of published news, laws, documents and scientific articles in a bibliographical research. The APA do Itapiracó consists of a conservation unit for sustainable use, located in the State of Maranhão, between the municipalities of São Luís and São José de Ribamar. This conservation unit represents an important fragment of the Amazon rainforest, which is characterized by its high biodiversity. Over the years, the process of human occupation in the area accelerated, becoming more intense. The Itapiracó area is part of an urban area with high housing density in the surroundings. A complex with leisure and sport areas was built in the area. The study has its importance in the social and academic environment, as it presents relevant information about conservation units and environmental protection. Understanding the reality of the APA of Itapiracó is the initial step to carry out continuous work in the future that involves environmental measures in the search for protection of the environment, such as the implementation of environmental education for civil society. DOI: https://doi.org/10.56238/tfisdwv1-074